Phylogenetic niche conservatism explains an inverse latitudinal diversity gradient in freshwater arthropods - Morinière, Jérôme (2016)
The underlying mechanisms responsible for the general increase in species richness from temperate regions to the tropics remain equivocal. Many hypotheses have been proposed to explain this astonishing pattern but additional empirical studies are needed to shed light on the drivers at work. Here we reconstruct the evolutionary history of the cosmopolitan diving beetle subfamily Colymbetinae, the majority of which are found in the Northern hemisphere, hence exhibiting an inversed latitudinal diversity gradient. We reconstructed a dated phylogeny using 12 genes, to investigate the biogeographical history and diversification dynamics in the Colymbetinae. We aimed to identify the role that phylogenetic niche conservatism plays in the inversed diversification pattern seen in this group. Our results suggest that Colymbetinae originated in temperate climates, which supports the hypothesis that their distribution is the result of an ancestral adaptation to temperate environmental conditions rather than tropical origins, and that temperate niche conservatism can generate and/or maintain inverse latitudinal diversity gradients.